2019
DOI: 10.1681/asn.2018080868
|View full text |Cite
|
Sign up to set email alerts
|

Early Acute Microvascular Kidney Transplant Rejection in the Absence of Anti-HLA Antibodies Is Associated with Preformed IgG Antibodies against Diverse Glomerular Endothelial Cell Antigens

Abstract: Background Although anti-HLA antibodies (Abs) cause most antibody-mediated rejections of renal allografts, non-anti-HLA Abs have also been postulated to contribute. A better understanding of such Abs in rejection is needed. MethodsWe conducted a nationwide study to identify kidney transplant recipients without anti-HLA donor-specific Abs who experienced acute graft dysfunction within 3 months after transplantation and showed evidence of microvascular injury, called acute microvascular rejection (AMVR). We deve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
89
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 91 publications
(103 citation statements)
references
References 38 publications
3
89
0
Order By: Relevance
“…At 4 months, the transplant biopsy showed mild inflammatory glomerular lesions (g1), no allograft glomerulopathy and only rare and focal sequelae of thrombotic microangiopathy. This case was classified by IDSMB as a rare case of acute humoral rejection without DSA, as recently described . The second patient presented venous graft thrombosis at day 1.…”
Section: Resultsmentioning
confidence: 73%
“…At 4 months, the transplant biopsy showed mild inflammatory glomerular lesions (g1), no allograft glomerulopathy and only rare and focal sequelae of thrombotic microangiopathy. This case was classified by IDSMB as a rare case of acute humoral rejection without DSA, as recently described . The second patient presented venous graft thrombosis at day 1.…”
Section: Resultsmentioning
confidence: 73%
“…Overall, these studies revealed a broad variety of antigens associated with rejection and chronic allograft injury. Most recently, Delville et al identified 38 patients with acute microvascular rejection in the absence of anti‐HLA antibodies in a French nationwide cohort of kidney transplant recipients. Microvascular inflammation serves as surrogate for an antibody‐mediated injury in the graft.…”
Section: Non‐hla Antibody Responsementioning
confidence: 99%
“…In recent years, multiple studies have been published showing a relation between the presence of non‐HLA autoantibodies and graft loss and/or rejection episodes . Although none of these studies have proven that autoantibodies actually contribute to the pathogenesis of graft dysfunction, the data indicate that detection of non‐HLA antibodies may be useful in identifying patients at risk for graft loss.…”
Section: Non‐hla Antibodies In Kidney Transplantationmentioning
confidence: 99%